Carbon Pricing Watch 2017 - World Bank; Ecofys (Washington, DC: World Bank, 2017)
The report is a one stop shop for learning about key developments and prospects of existing and emerging carbon initiatives. There is a continued momentum for carbon pricing. As of 2017, over 40 national and 25 subnational jurisdictions representing almost a quarter of global greenhouse gas emissions are putting a price on carbon. Over the past decade the number of jurisdictions with carbon pricing initiatives have doubled. On average, carbon pricing initiatives cover about half of the emissions in these jurisdictions, which translates to a total coverage of about 8 Gigatons of carbon dioxide or about 15% of global emissions (a fourfold increase over the past decade).